2020
DOI: 10.1093/pubmed/fdz163
|View full text |Cite
|
Sign up to set email alerts
|

Current status of official WeChat accounts for public health education

Abstract: Background To investigate the current use status of official WeChat accounts for the Centers for Disease Control and Prevention in public health education and relevant factors that can impact the effectiveness of message delivery. Methods A retrospective survey was conducted to evaluate the effectiveness of official WeChat accounts. About 531 official WeChat accounts and 50 939 articles were analyzed using a cluster sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 9 publications
0
32
0
Order By: Relevance
“…This concurs with empirical observations that many social media accounts (e.g., Twitter, WeChat, Microblog, etc.) have been used to release real-time epidemic information to the public in the outbreak of COVID-19 pandemic ( Roy et al, 2020 ; Sun et al, 2020 ).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…This concurs with empirical observations that many social media accounts (e.g., Twitter, WeChat, Microblog, etc.) have been used to release real-time epidemic information to the public in the outbreak of COVID-19 pandemic ( Roy et al, 2020 ; Sun et al, 2020 ).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…The number of consultation items has significantly increased over a short period, which may be related to the attitude toward the public's unknown and panic psychology at the early stage of the outbreak [11], which needed to be addressed by medical experts providing professional answers and psychological counseling. Multiple studies [12][13][14][15] have revealed that WeChat consultation services can deliver effective, convenient, and timely help to the general public.…”
Section: Discussionmentioning
confidence: 99%
“…One of the WeChat mini-app prototypes was adapted for use in the current study. WeChat (Android and iOS) is a social platform in China with over one billion active users (52) that has been widely used for public health education by Chinese health administrations and private organizations (53). The WeChat app allows developers to build new app programs (i.e.…”
Section: Methods and Analysismentioning
confidence: 99%